Sloshing effect analysis of liquid storage tank under seismic excitation. (September 2022) - Luo, Dongyu; Liu, Chunguang; Sun, Jiangang; Cui, Lifu; Wang, Zhen
Abstract: Sloshing wave height is a main parameter in the seismic design of liquid storage tanks, and severe sloshing may lead to the liquid leakage or buckling of the steel tank wall. To accurately evaluate the sloshing wave height of the tank under earthquake action, a total of three shaking table tests were conducted on the liquid storage tanks, and numerical simulation methods based on the direct coupling method as well as the bidirectional coupling method were implemented. The sloshing height results from tests and simulations were compared with the values obtained from the theoretical formula, and the applicability of various calculation methods was analyzed. Thereafter, the theoretical formula of the simplified mechanical model and the bidirectional coupling method were adopted to predict the sloshing wave height of tanks with various dimensions, and the theoretical formula was further modified. Simultaneously, the influence of pulse-like ground motion on sloshing effect and hydrodynamic pressure of large-scale liquefied natural gas (LNG) storage tanks was examined. Additionally, the GB 50341–2014, API 650–2013, and Eurocode 8–2006 were utilized to assess the sloshing wave height of large storage tanks subjected to seismic ground motion, and the applicability of the computed results has been further discussed. Based on the above research, practical design recommendations were proposed in this work, which can provide a guidance for the seismic design of storage tanks.